Guide Flange Prosthesis: A Case Report - D. Padmini; B. L. Rao; C. D. Sai Kumar; T. L. G. Sravanthi; G. Krishna Teja; Karuna Murali (Archives of Current Research International, 2023)
Patients who have undergone surgical hemi/segmental/subtotal mandibulectomy for various reasons with resulting mandibular deviation are given a guide flange. If secondary osseous grafting is planned, the doctor must wait for the graft, lesion, or radiotherapeutic effects to resolve. A definitive prosthesis can be planned only when the graft has been healed. During this time lag, the patient must be fitted with a prosthesis to rectify mandibular deviation caused by unilateral muscle strain. Furthermore, in some circumstances, a definitive prosthesis must be postponed due to bone grafting failure or the patient’s unwillingness to undergo a second surgery. This clinical case report shows a mandibular guide flange prosthesis fabricated for a patient.